2008
DOI: 10.1029/2007jd009313
|View full text |Cite
|
Sign up to set email alerts
|

Isotope ratios of precipitation and water vapor observed in Typhoon Shanshan

Abstract: [1] Isotope ratios of precipitation and water vapor were observed during the passage of Typhoon Shanshan at Ishigaki Island, southwestern Japan, on 15-16 September 2006. Such high-resolution isotopic observations allow for qualitative understanding of atmospheric moisture cycling; they revealed that isotope ratios of both the precipitation and water vapor decreased radially inward in the cyclone's outer region; anomalously high isotope ratios appeared in the cyclone's inner region; and d-excess tended to decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 28 publications
5
83
0
1
Order By: Relevance
“…Sugimoto and Higuchi (1988) reported large (small) decreases in precipitation isotope ratios when the precipitation intensity was high (low). Fudeyasu et al (2008) found increases in the isotope ratios of precipitation accompanying a tropical cyclone eyewall. Dansgaard (1953) observed that isotopic ratios in precipitation did not vary with time throughout a rain shower.…”
Section: Stable Hydrogen and Oxygen Isotope Ratios (D 2 H And Dmentioning
confidence: 99%
“…Sugimoto and Higuchi (1988) reported large (small) decreases in precipitation isotope ratios when the precipitation intensity was high (low). Fudeyasu et al (2008) found increases in the isotope ratios of precipitation accompanying a tropical cyclone eyewall. Dansgaard (1953) observed that isotopic ratios in precipitation did not vary with time throughout a rain shower.…”
Section: Stable Hydrogen and Oxygen Isotope Ratios (D 2 H And Dmentioning
confidence: 99%
“…Another serious problem is that the inner structure of the TC is not resolved because, in K2014, the ICM incorporates an external meteorological data set derived from a global atmospheric reanalysis with a horizontal grid of 1.25° longitude by 1.25° latitude. If we also consider the results of Fudeyasu et al (2008), who observed the isotope ratios of precipitation and water vapor during the passage of a typhoon, we may, thus, underestimate the proportion of underlying ocean vapor to total precipitable water in the vicinity of the TC's center.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the strong southerly flow of typhoons brings heavy rainfall, which has extremely low isotopic contents (e.g., Fudeyasu et al 2008). Thus, we ignored typhoon years (1963, 1965, 1966 and 1974) from the analysis (shaded in blue in Fig.…”
mentioning
confidence: 99%